Pengaruh Model Pembelajaran Problem Based Learning Menggunakan Vidio Pembelajaran Berbasis Artificial Intelligence (AI) Terhadap Hasil Belajar Siswa Pada Materi Sistem Pencernaan Manusia di Kelas XI MIA SMA Swasta Muhammadiyah 10 Rantauprapat - Syahputra, Dicky Ananda; Harahap, Hasmi Syahputra; Khairul,; Sari, Novi Fitriandika (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyze the effect of implementing Problem-Based Learning (PBL) assisted by Artificial Intelligence (AI)-based video on students’ learning outcomes in the topic of the human digestive system. The research employed a quasi-experimental method with a Pretest-Posttest Control Group Design. The participants of the study were eleventh-grade students of SMA Swasta Muhammadiyah 10 Rantauprapat. The instruments used in this study included a learning achievement test and a student response questionnaire. Data were analyzed using the t-test. The results show that the application of the Problem-Based Learning learning model with the help of Artificial Intelligence (AI)-based videos is proven effective in improving student learning outcomes on the human digestive system material. This is seen from the increase in the average score, the lowest score, and the highest score, and is supported by the results of normality tests, homogeneity tests, and One Sample Tests that show significant differences. The implication of this finding is the need for educators to not only rely on conventional learning, but also combine it with innovative learning strategies or media. The combination of the two is believed to increase the effectiveness of learning and student motivation.